An informatics research agenda to support precision medicine: seven key areas. (23rd April 2016) - Tenenbaum, Jessica D; Avillach, Paul; Benham-Hutchins, Marge; Breitenstein, Matthew K; Crowgey, Erin L; Hoffman, Mark A; Jiang, Xia; Madhavan, Subha; Mattison, John E; Nagarajan, Radhakrishnan; Ray, Bisakha; Shin, Dmitriy; et al.
Abstract: The recent announcement of the Precision Medicine Initiative by President Obama has brought precision medicine (PM) to the forefront for healthcare providers, researchers, regulators, innovators, and funders alike. As technologies continue to evolve and datasets grow in magnitude, a strong computational infrastructure will be essential to realize PM's vision of improved healthcare derived from personal data. In addition, informatics research and innovation affords a tremendous opportunity to drive the science underlying PM. The informatics community must lead the development of technologies and methodologies that will increase the discovery and application of biomedical knowledge through close collaboration between researchers, clinicians, and patients. This perspective highlights seven key areas that are in need of further informatics research and innovation to support the realization of PM.